Liberals, Conservatives, and Mavericks: On Christian Churches of Eastern Europe since 1980 - Ramet, Sabrina P. (Central European University Press, 2024)
No Church is monolithic—this is the preliminary premise of this volume on the public place of religion in a representative number of post-communist countries. The studies confirm that within any religious organization we can expect to find fissures, factions, theological or ideological quarrels, and perhaps even competing interest groups, such as missionary workers, regular clergy versus secular clergy, and sometimes even competing ecclesiastical hierarchies. The main focus of the book rests on the divisions arising within select Christian Churches, as they confront the processes of secularization and atheization. The coverage area includes Russia and the Ukraine, East-Central Europe and South-Eastern Europe. Some chapters focus on individual clergy who challenge the mainstream of their given Church either from a more liberal or from a more conservative perspective, while others deal with the divisive forces impacting the religious organizations. This festschrift to honor Sabrina Ramet’s seminal contribution to the study of religion in the politics of the communist and post-communist world, brings together several generations of scholars from a variety of countries, both those well established in their fields of study as well as young promising academics.